Estimating catastrophic costs due to pulmonary tuberculosis in Bangladesh - Chowdhury, AS; Ahmed, MS; Ahmed, S; Khanam, F; Farjana, F; Reza, S; Islam, S; Islam, A; Khan, JAM; Rahman, M (Atlantis Press, 2020)
To eliminate TB from the country by the year 2030, the Bangladesh National Tuberculosis (TB) Program is providing free treatment to the TB patients since 1993. However, the patients are still to make Out-of-their Pocket (OOP) payment, particularly before their enrollment Directly Observed Treatment Short-course (DOTS). This places a significant economic burden on poor-households. We, therefore, aimed to estimate the Catastrophic Health Expenditure (CHE) due to TB as well as understand associated difficulties faced by the families when a productive family member age (15–55) suffers from TB. The majority of the OOP expenditures occur before enrolling in. We conducted a cross-sectional study using multistage sampling in the areas of Bangladesh where Building Resources Across Communities (BRAC) provided TB treatment during June 2016. In total, 900 new TB patients, aged 15–55 years, were randomly selected from a list collected from BRAC program. CHE was defined as the OOP payments that exceeded 10% of total consumption expenditure of the family and 40% of total non-food expenditure/capacity-to-pay. Regular and Bayesian simulation techniques with 10,000 replications of re-sampling with replacement were used to examine robustness of the study findings. We also used linear regression and logit model to identify the drivers of OOP payments and CHE, respectively. The average total cost-of-illness per patient was 124 US$, of which 68% was indirect cost. The average CHE was 4.3% of the total consumption and 3.1% of non-food expenditure among the surveyed households. The poorest quintile of the households experienced higher CHE than their richest counterpart, 5% vs. 1%. Multiple regression model showed that the risk of CHE increased among male patients with smear-negative TB and delayed enrolling in the DOTS. Findings suggested that specific groups are more vulnerable to CHE who needs to be brought under innovative safety-net schemes.